North Korea through the Looking Glass - Oh, Kong Dan (Book collections on Project MUSE., 2000)
Oh and Hassig draw on ten years of research about the small militarized state, whose culture is dominated by the official ideology of Juche, emphasizing self-reliant independence and worship of the supreme leader, General Kim Jong II. However, a collapsed economy and sensitive nuclear proliferation in the militaristic society have led to fear and anachronistic policies, retarding the social and political growth of the country.